Differences in Results of Examination of Urine Protein Levels Dipstik Method with 6% Acetic Acid Method in Patients with Diabetes Mellitus in Area Puskesmas Baturraden II - Rahayu, Feni Putri; Sulistiyowati, Retno ,; Sudarsono, Tantri Analisawati; Rahaju, Minto (Poltekkes Kemenkes Mataram, 2023)
Diabetes Mellitus (DM) is a non-communicable disease and a major public health issue in Indonesia and around the world. Proteinuria caused by diabetes in the blood vessels can cause kidney damage. Diabetes can also cause nerve damage in the body. This can make urinating difficult. The pressure caused by a full bladder can harm the kidneys. If urine remains in the bladder for a longer duration, it can cause an infection due to the rapid growth of bacteria in urine with a high sugar level, even if the presence of protein in the urine has been tested in a laboratory. Objective: The study aimed to determine the difference in the results of urine protein examination with the dipstick method with the 6% acetic acid method in DM patients in the working area of Puskesmas (Public Health Center) Baturraden II. Methods: The research design used was analytic observational with a cross-sectional study. Thirty urine samples were used with purposive sampling as the sampling technique. Chi-Square Test was employed for Statistical Analysis. The results of the tests produced a significant value of 0.000 (P 0,0 5), indicating that the p-value was lower in relation to the degree of error. It could be concluded that the results of urine protein examination using the dipstick method and the 6% acetic acid method differed in DM patients.